2007
DOI: 10.1111/j.1365-2929.2006.02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Does teaching style matter? A randomised trial of group discussion versus lectures in orthopaedic undergraduate teaching

Abstract: We found that interactive teaching styles are more popular than didactic lectures in undergraduate orthopaedic and trauma teaching. We also found some evidence that knowledge retention is better following an interactive teaching style.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 6 publications
11
73
1
1
Order By: Relevance
“…Some literature supports interactive teaching methodologies as promoting increased understanding and application of knowledge as well as retention of factual knowledge (Costa, Rensburg, & Rushton, 2007). Although case studies have been used as educational tools for over 100 years in a variety of disciplines, a dearth of information exists in the research nursing literature regarding their use, construct, and outcomes (Delpier, 2006).…”
Section: Case Studymentioning
confidence: 99%
“…Some literature supports interactive teaching methodologies as promoting increased understanding and application of knowledge as well as retention of factual knowledge (Costa, Rensburg, & Rushton, 2007). Although case studies have been used as educational tools for over 100 years in a variety of disciplines, a dearth of information exists in the research nursing literature regarding their use, construct, and outcomes (Delpier, 2006).…”
Section: Case Studymentioning
confidence: 99%
“…So, these problems need to be resolved due to the importance of programming courses and should be addressed with special care [24,25]. Moreover, educational theory and innovative educational technologies suggest that lecture based classes may not be the best way to impart knowledge of students [26,27,28]. So, it is important to reexamine the impact and requirement of formal regular lecture sessions in connection with programming courses.…”
Section: Introductionmentioning
confidence: 99%
“…38 Interestingly, the bottom ranked quality was interactive teaching style, which is viewed by many scholars as highly valued by students and beneficial in terms of academic achievements. [39][40][41] A closer look at the teacher qualities students preferred revealed that on the whole, the highly valued qualities were those that reflected teacher engagement with the learning process where the emphasis was on the level of teacher commitment to the task of optimizing student learning and achievement. The least-valued qualities, on the other hand, were those that reflected student engagement with the learning process, where the emphasis was on student commitment to optimizing their own learning and achievement.…”
Section: Discussionmentioning
confidence: 99%